Strategic Investment in a Debt Bargaining Framework. (IMF Working Papers; Working Paper, 1989)
This paper analyzes the strategic role of investment from a debtor country's perspective. The framework is one in which, if the debtor country is unable to meet debt obligations, a bargaining regime determines the amount of debt repayment. In the context of a two-country real trade model, debt repayment is equal to the trade surplus of the debtor. The outcome of the bargaining game will therefore be dependent (among other things) on the level of production in the debtor country. In this framework, the paper shows that productive investment may increase or decrease the bargaining power of the debtor country. This ambiguity appears to be fairly robust.